FUNGSI PENGAWASAN PEMERINTAH KOTA PEKANBARU TERHADAP LIMBAH MEDIS BALAI KESEHATAN/POLIKLINIK DI KECAMATAN TAMPAN - Rizal . (Jurnal Renaissance, 2017)
In order to support the Pekanbaru Municipal Government in carrying out the supervision function on medical waste, the health clinic / polyclinic should be based on effective supervision. For that needed support and commitment from the leadership in the supervision of medical waste health clinic/polyclinic. However, in the implementation of the supervisory function, there are still weaknesses that cause ineffective supervisory function, this is indicated by the findings of each health center/polyclinic does not manage its medical waste well and does not complement UKL-UPL Document. In response to the problems of the Pekanbaru City Government's monitoring function on the medical waste of the health clinic/clinic in Sub District Tampan, the researcher uses Sarwoto's theory including : Accurate, Timely, Objective and Thorough, Centralized, Realistically Economical, Organistally Realistic, Coordinated with Workflow, Flexible, As a guide and operational, and Accepted members of the organization.Key Words: Supervision Function; Medical Waste Health Center;                  Polyclinic